Evaluating the impact of government policies on tourist satisfaction in Vietnam: A Generalized Structured Component Analysis (GSCA) approach - Canh Quang Tran (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2025)
This research evaluates the impact of government policies on tourist satisfaction in Vietnam using Generalized Structured Component Analysis. It explores critical factors like infrastructure development, environmental conservation, safety, and cultural preservation, identifying them as key determinants of tourist satisfaction. The study highlights the essential role of government initiatives in these areas to improve the tourist experience. Findings indicate that effective policies in infrastructure, environmental protection, and cultural heritage preservation are crucial for sustainable tourism growth. Ensuring safety and security fosters trust and encourages repeat visits. These insights provide practical recommendations for policymakers and industry stakeholders to develop strategies that enhance tourist satisfaction and strengthen Vietnam’s competitive position in the global tourism market. Collaboration among government authorities, private entities, and local communities is essential to address these challenges. By prioritizing sustainable tourism practices and aligning policies with tourist expectations, Vietnam can achieve long-term growth in its tourism sector while preserving cultural and natural assets. This study offers a comprehensive framework for understanding the relationship between government policies and tourist satisfaction, aiding strategic planning and policy formulation to enhance Vietnam’s appeal as a premier travel destination.